The Effect Of Down Payment Policy to Level of Credit Sales Volume PT. Pegadaian (Persero) - Aris Baharuddin; Nur Amalia Ramdlani Azis (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of down payment policies on the volume level of motorcycle credit sales at PT. Pegadaian (Persero) branch office of Daya. This study uses a quantitative approach, descriptive research type, with a research population of 81 customers and the sample in this study was taken from a large population of 81 customers. Data collection techniques used are through observation, questionnaires (questionnaire), and documentation. The data that has been obtained from the research results are processed using data analysis and using the SPSS.22 software application which consists of validity and reliability tests, descriptive analysis techniques and inferential statistical analysis.